Penerapan Akuntansi Pertanggungjawaban sebagai Alat Penilaian Kinerja Pusat Biaya - Wasih Latuh Rahmi; Daffa Ulhaq; Nurkhofifah Nst (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of this research is to compare and evaluate how to use the answer accounting system to measure how a company's management capabilities are. This journal uses qualitative research methods by expressing an estimate by evaluating, reviewing, then making conclusions for problems that occur as temporary answers. As for the results in this journal it is known that when it was implemented, the organizational structure of PT. Bangun Kubah Sarana has clearly shown that the authorities and responsibilities are according to organizational levels, but the central code has not yet been established, the budgeting system is carried out using the Bottim Up Budgeting method, which starts from the lowest manager level and continues to the highest level, which is explained in detail. In the preparation of accountability reports on the cost account code, there is still no separation between controlled and uncontrollable costs. Therefore, in order to implement an accounting system, it is necessary to separate controllable costs from uncontrollable costs, while the results of the analysis in this journal show that by implementing a responsibility accounting system, management will more easily evaluate performance.